The effect of soft tissue mobilization techniques on the symptoms of chronic posterior compartment syndrome in runners : a multiple case study approach - Kruger, P.E. (Pieter Ernst) (University of Pretoria, 2013)
Thesis (DPhil)--University of Pretoria, 2008.